Analysis of Information Security Readiness Using the Index KAMI (Decode: Jurnal Pendidikan Teknologi Informasi, 2024)
Hospitals are institutions that store sensitive data. Information security needs to be implemented and audited regularly. Evaluation of information security can use the KAMI Index to determine the readiness of the application of information technology in terms of information security. Research shows that PKU Muhammadiyah Surakarta scores 31 on the electronic system assessment and 356 on the five implementation aspects. These results indicate that PKU Muhammadiyah Surakarta is in a position to implement the framework, so it is necessary to develop both technical and non-technical to be more prepared to face the digitalization era. The results of this study indicate that the KAMI index can be used as a tool and method in measuring information security readiness towards ISO 27001:2013. Based on the evaluation of the level of information security at PKU Muhammadiyah Surakarta, it is in the high category with a score of 31. The assessment of the five aspects gets a score of 356, so it is still at the stage of fulfilling the basic framework and at maturity levels I+ to II. PKU Muhammadiyah Surakarta should regularly evaluate its information security to assess progress in the five key areas outlined in the ISO 27001/SNI information security standards.